Metabolic Flexibility and Mitochondrial Bioenergetics in the Failing Heart. Therapeutic Approaches - Mariana G. ROSCA (Sciendo, 2021)
Objectives. We will review current concepts regarding bioenergetic decline in heart failure (HF). In the heart, the high energy demand must be met by continuous ATP generation. Cardiac energetic machinery orchestrates the ATP production by using oxidation of multiple energetic substrates including fatty acids (FA), glucose, amino acids and ketone bodies. The normal heart is metabolically flexible and able to use different energetic fuels during physiologic or pathologic circumstances to better match the energy demand. Mitochondria have critical role in maintaining cardiac metabolic flexibility. Methods. We analyzed the scientific literature pertinent to HF and mitochondrial dysfunction. Results. The general consent is that metabolic fl exibility is lost in HF with either preserved or reduced ejection fraction (HFpEF and HFrEF, respectively). The prototype of HFpEF is the metabolic heart disease that is characterized by increased reliance on FA oxidation for ATP production and decreased glucose oxidation, while HFrEF presents a decreased FA oxidation. Both types of HF are associated with a decline in mitochondrial function leading to increased oxidative stress, abnormalities in the redox status and energy deficit. Conclusion. Current research is committed to find novel metabolically targeted therapeutic approaches to improve energetic metabolism and alleviate HF progression.